2013
DOI: 10.1002/tect.20088
|View full text |Cite
|
Sign up to set email alerts
|

Multistage magma emplacement and progressive strain accumulation in the shallow‐level Krkonoše‐Jizera plutonic complex, Bohemian Massif

Abstract: [1] Field relationships combined with new U-Pb zircon geochronology suggest that the shallow-level Krkonoše-Jizera plutonic complex, northern Bohemian Massif, was assembled successively from bottom to top, starting with emplacement of the separately evolved S-type Tanvald granite (317.3 ± 2.1 Ma), followed by at least two voluminous batches of the I-type porphyritic Liberec (319.5 ± 2.3 Ma) and Jizera (320.1 ± 3.0 Ma and 319.3 ± 3.7 Ma) granites. The intrusive sequence was completed by uppermost, minor intrusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 117 publications
(119 reference statements)
0
24
0
1
Order By: Relevance
“…It shows the close spatial relationships of shallow-level plutonic bodies with volcanic or subvolcanic facies. The Křenov ignimbrite/tuff complex (312.39 ± 0.10 Ma) overlaps in age with 312.5 ± 0.3 to 312.2 ± 0.3 Ma ID-TIMS ages (Kryza et al 2014) of S-type granites of the Krkonoše-Jizera Pluton (Žák et al 2013(Žák et al , Kusiak et al 2014, Pluton. SHRIMP U-Pb zircon ages of 312.8 ± 2.8 Ma and 312.4 ± 4 Ma for andesite dykes and lamprophyres cutting older acid volcanic and subvolcanic rocks, suggest that mantle-derived mafic melts are closely spatio-temporaly related to the crustally-derived acid melts.…”
Section: Volcanic Activity Of the Intra-sudetic And Krkonoe-piedmont mentioning
confidence: 99%
“…It shows the close spatial relationships of shallow-level plutonic bodies with volcanic or subvolcanic facies. The Křenov ignimbrite/tuff complex (312.39 ± 0.10 Ma) overlaps in age with 312.5 ± 0.3 to 312.2 ± 0.3 Ma ID-TIMS ages (Kryza et al 2014) of S-type granites of the Krkonoše-Jizera Pluton (Žák et al 2013(Žák et al , Kusiak et al 2014, Pluton. SHRIMP U-Pb zircon ages of 312.8 ± 2.8 Ma and 312.4 ± 4 Ma for andesite dykes and lamprophyres cutting older acid volcanic and subvolcanic rocks, suggest that mantle-derived mafic melts are closely spatio-temporaly related to the crustally-derived acid melts.…”
Section: Volcanic Activity Of the Intra-sudetic And Krkonoe-piedmont mentioning
confidence: 99%
“…It is built mainly of Proterozoic to Early Palaeozoic Construction of new houses on a uranium vein outcrop: a case study from the Czech Republic metamorphic rocks. The area is penetrated by the large Krkonoše-Jizera (K-J) granite pluton of the Carboniferous age (317-320 Ma) [7]. The south--western part of the K-J pluton is composed of Tanvald alkaline granite, which differs geochemically and also by the content of radioactive elements; it is a real 'uranium granite'.…”
Section: Occurrence Of Uranium Mineralization At a Construction Sitementioning
confidence: 99%
“…Research regarding the structural record emplacement mechanisms and growth of magmatic plutons represents an integral part of the decadelong effort of earth scientists to understand magmatic systems, exchange of matter, and heat in the lithosphere and tectonic evolution of regions including magmatic activity. The mode of emplacement and internal flow dynamics of concentrically zoned granitic plutons has been recently discussed in terms of pulse-like, incremental growth by amalgamation of successive melt batches (Barboni et al, 2013;Leuthold et al, 2012;Stearns & Bartley, 2014;Miller et al, 2011;Žák et al, 2013) rather than emplacement of large volumes of magma at once (Marsh, 1982;Miller & Paterson, 1999;Paterson & Vernon, 1995;Weinberg, 1996;Weinberg & Podladchikov, 1994). Paterson and Vernon (1995) suggested that the fabric pattern in such granitic bodies, also called concentrically expanded plutons (CEPs), do not reflect ballooning in terms of late inflation of a diapirically ascended pluton (Mahon et al, 1988;Marsh, 1982;Ramberg, 1972), but were emplaced as syntectonic nested diapirs.…”
Section: Introductionmentioning
confidence: 99%